Overview of diagnostic tools and nano-based therapy of SARS-CoV-2 infection - Bhattacharjee B.; Rynjah D.; Ahmed A.B.; Newar A.; Sengupta S.; Chakrabarty S.; Sahu R.K.; Khan J. (My University, 2025)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a highly infectious virus that belongs to the RNA virus family Coronaviridae, infects a variety of animal species, and replicates primarily in the lower and upper respiratory tract. A proportion of 90% of infections are uncomplicated, and 4–7% of people are hospitalized. The main focus is on people with comorbidities, which are risk factors for severe disease and lead to high rates of hospitalization and death. During the early stages of a pandemic, many diagnostic approaches such as biochemical, serological, and molecular investigations are used to detect SARS-CoV-2. This review emphasizes immunodiagnostic techniques, including virus neutralization assay, CRISPR, nicking endonuclease amplification reaction, lateral flow immunoassay, protein-peptide microarray, and chemiluminescence immunoassay; it also includes novel approaches such as next-generation sequencing. Nanotechnology is critical in the prevention, diagnosis, and treatment of SARS-CoV-2, with an in-depth review of its principles, usefulness, benefits, and drawbacks. The study sheds light on diagnostic methods that apply to future infectious viruses as well as SARS-CoV-2. Furthermore, the article explores diverse nano-based treatments, including vaccines, immunotherapy, and gene therapy, providing encouraging methods for the prevention and management of SARS-CoV-2. © The Author(s), under exclusive licence to the Institute of Chemistry, Slovak Academy of Sciences 2024.